Minimal relapse risk and early normalization of survival for patients with Burkitt lymphoma treated with intensive immunochemotherapy: an international study of 264 real‐world patients. (4th February 2020) - Jakobsen, Lasse H.; Ellin, Fredrik; Smeland, Knut B.; Wästerlid, Tove; Christensen, Jacob H.; Jørgensen, Judit M.; Josefsson, Pär L.; Øvlisen, Andreas K.; Holte, Harald; Blaker, Yngvild N.; Grauslund, Jacob H.; Bjørn, Jon; et al.
Summary: Non‐endemic Burkitt lymphoma (BL) is a rare germinal centre B‐cell‐derived malignancy with the genetic hallmark of MYC gene translocation and with rapid tumour growth as a distinct clinical feature. To investigate treatment outcomes, loss of lifetime and relapse risk in adult BL patients treated with intensive immunochemotherapy, retrospective clinic‐based and population‐based lymphoma registries from six countries were used to identify 264 real‐world patients. The median age was 47 years and the majority had advanced‐stage disease and elevated LDH. Treatment protocols were R‐CODOX‐M/IVAC (47%), R‐hyper‐CVAD (16%), DA‐EPOCH‐R (11%), R‐BFM/GMALL (25%) and other (2%) leading to an overall response rate of 89%. The two‐year overall survival and event‐free survival were 84% and 80% respectively. For patients in complete remission/unconfirmed, the two‐year relapse risk was 6% but diminished to 0·6% for patients reaching 12 months of post‐remission event‐free survival (pEFS12). The loss of lifetime for pEFS12 patients was 0·4 (95% CI: −0·7 to 2) months. In conclusion, real‐world outcomes of adult BL are excellent following intensive immunochemotherapy. For pEFS12 patients, the relapse risk was low and life expectancy similar to that of a general population, which is important information for developing meaningful follow‐up strategies with increased focus on survivorship and less focus on routine disease surveillance.